2013
DOI: 10.3389/fimmu.2013.00148
|View full text |Cite
|
Sign up to set email alerts
|

The Vitamin D Receptor and T Cell Function

Abstract: The vitamin D receptor (VDR) is a nuclear, ligand-dependent transcription factor that in complex with hormonally active vitamin D, 1,25(OH)2D3, regulates the expression of more than 900 genes involved in a wide array of physiological functions. The impact of 1,25(OH)2D3-VDR signaling on immune function has been the focus of many recent studies as a link between 1,25(OH)2D3 and susceptibility to various infections and to development of a variety of inflammatory diseases has been suggested. It is also becoming i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
202
2
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 257 publications
(225 citation statements)
references
References 119 publications
4
202
2
7
Order By: Relevance
“…These actions are mediated by activating vitamin D receptors (VDR) of T-cells [16,17]. It is also becoming increasingly clear that microbes slow down immune reactivity by deregulating the VDR ultimately to increase their chance of survival [18]. Moreover, vitamin D streamlines the inflammatory cascade by regulating the nuclear factor kappa B (NF-κB) which is induced by activation of pathogen associated molecular patterns (PAMPs) derived from pathogens like protozoa, viruses, bacteria, and fungi.…”
Section: Role Of Vitamin D In Infection and Immunitymentioning
confidence: 99%
“…These actions are mediated by activating vitamin D receptors (VDR) of T-cells [16,17]. It is also becoming increasingly clear that microbes slow down immune reactivity by deregulating the VDR ultimately to increase their chance of survival [18]. Moreover, vitamin D streamlines the inflammatory cascade by regulating the nuclear factor kappa B (NF-κB) which is induced by activation of pathogen associated molecular patterns (PAMPs) derived from pathogens like protozoa, viruses, bacteria, and fungi.…”
Section: Role Of Vitamin D In Infection and Immunitymentioning
confidence: 99%
“…The genomic mechanism is determined by intracellular VDR that heterodimerizes with retinoic X receptor after binding to active VitD. This heterodimer is then translocated to the nucleus leading to activation or inhibition of a vast diversity of genes [5].…”
Section: Vitd Metabolismmentioning
confidence: 99%
“…The biological activity of Vitamin D is thus dependent both on the adequate production and distribution of 1, 25 (OH) 2 D 3 as well as adequate expression of VDR [1]. In individuals with functioning VDR, 1,25(OH) 2 D 3 has been considered a therapeutic agent for the treatment of periodontal inflammation [43].…”
Section: Vdr Agonistsmentioning
confidence: 99%
“…There has been an explosion of scientific evidence which suggests the profound role that vitamin D plays in immune homeostasis. Vitamin D nuclear Receptor (VDR) has been identified as a ligand-dependent transcription factor which, in concert with its endogenous ligand, 1,25 hydroxivitamin D (1,25(OH) 2 D 3 ), is involved in the expression of countless genes [1]. In view of recent research which revealed that most immune cells express the vitamin D nuclear receptor (VDR) [2][3][4][5], the authors reviewed the current knowledge regarding the immunomodulatory effects of vitamin D through its VDR on peridondontal disease.…”
Section: Introductionmentioning
confidence: 99%